Stereotactic ablative radiotherapy for malignant mediastinal and hilar lymphadenopathy: a systematic review - Tjong, Michael C. (J Thorac Dis, 2020)
BACKGROUND: Stereotactic ablative radiotherapy (SABR) safety and efficacy for mediastinal and hilar lymphadenopathy (MHL) is not yet established, given its potential for toxicity due to the proximity to esophagus and proximal bronchial tree (PBT). This review summarized current reported outcomes of MHL SABR. METHODS: This systematic review, based on the PRISMA guidelines, was performed using MEDLINE® (PubMed®), EMBASE and Cochrane Library databases from inception until December 2018. Studies reporting outcomes from SABR specifically for MHL from all primary malignancies were included. Non- English studies, guidelines, reviews, non-peer reviewed correspondences were excluded. Only the most recent publication and/or largest cohort from a single institution would be included for analysis. RESULTS: From the 222 studies identified, 4 retrospective studies totaling 196 patients were included in the analysis. One study included a small number of patients receiving non-ablative doses of stereotactic radiotherapy (RT). Non-small cell lung cancer (NSCLC) was the most common primary (65%), followed by breast (8%). Median follow-up ranged between 12 and 32 months. Reported dose and fractionation ranged from 21 to 60 Gy in 3–11 fractions, with median BED10 ranged from 46–106 Gy10. Three studies reported local control (LC) rates: study 1, 97% (1-year) and 77% (5-year); study 4, 88% (2-year); and study 2, 69% (6-month) and 66% (16-month). Pooled grade 3–5 toxicity rate according to Common Terminology Criteria for Adverse Events (CTCAE) v4.0 was 6% (n=11). Pooled SABR-related mortality (grade 5 toxicity) rate was 2% (n=4). Three SABR-related deaths from esophageal fistulae (2 to trachea, 1 to mediastinum) were reported, with all 3 having prior RT to the subcarinal nodes. CONCLUSIONS: Our review suggested SABR for MHL to be feasible and effective, though there is a potential for serious toxicity especially in the re-irradiation scenario. Multi-institutional and/or prospective studies will help determine the therapeutic benefit of SABR in this high-risk treatment scenario.